2018
DOI: 10.1063/1.5038615
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment of In2O3/β-Ga2O3 interface determined by X-ray photoelectron spectroscopy

Abstract: The energy band alignment of the atomic-layer-deposited In2O3/β-Ga2O3 (2¯01) interface is evaluated by X-ray photoelectron spectroscopy. The X-ray diffraction pattern reveals that the In2O3 film grown at 160 °C is amorphous, while it becomes polycrystalline at a higher deposition temperature of 200 °C. The bandgaps, determined by reflection electron energy loss spectroscopy, are 4.65, 3.85, and 3.47 eV for β-Ga2O3, polycrystalline In2O3, and amorphous In2O3, respectively. Both amorphous and polycrystalline In2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…[51,52,[54][55][56][57][58][59][60][61][62][63][64], the present mixed-phase Ga 2 O 3 films had a large band offset including ∆E V and ∆E C compared with previous research. The band offset of m-Ga 2 O 3 film in the present study completely meets the interface's requirements for the driving force of separating electron-hole pairs.…”
contrasting
confidence: 55%
“…[51,52,[54][55][56][57][58][59][60][61][62][63][64], the present mixed-phase Ga 2 O 3 films had a large band offset including ∆E V and ∆E C compared with previous research. The band offset of m-Ga 2 O 3 film in the present study completely meets the interface's requirements for the driving force of separating electron-hole pairs.…”
contrasting
confidence: 55%
“…However, single-crystalline indium oxide (In2O3), an intrinsically n-type transparent conducting oxide (TCO) layer with an optical bandgap of ~3.7 eV, [45][46][47] has the potential to achieve the aforementioned goals and emerge as the material of choice as a conducting interfacial layer between the Ga2O3 and Al2O3 platforms. Recently, Sun et al 46 demonstrated type-I band alignment with narrow conduction-band offset (CBO) and valence-band offset (VBO) of 0.35 and 0.45 eV, respectively, at the polycrystalline β-Ga2O3/In2O3 interface, elucidating the potential of the above heterostructure for reducing the barrier height and enhancing carrier transport in visible-transparent oxide platforms. Similarly, Zhi et al 47 demonstrated an even lower CBO of 0.07 eV in the type-I heterostructure for a pulsed laser deposition (PLD)-grown polycrystalline Ga2O3/In2O3 heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Although using interfacial metal layers or other two-dimensional materials (e.g., transition metal dichalcogenides, hexagonal boron nitride, and graphene , ) could provide the required electrical and optical properties, those methods rely on chemical vapor deposition (CVD), thermal evaporation, and sputtering and typically result in polycrystalline structures that are not ideal for the subsequent growth of high-quality crystal structures. However, single-crystalline indium oxide (In 2 O 3 ), an intrinsically n -type transparent conducting oxide (TCO) layer with an optical band gap of ∼3.7 eV, has the potential to achieve the aforementioned goals and emerge as the material of choice as a conducting interfacial layer between the Ga 2 O 3 and Al 2 O 3 platforms. Recently, Sun et al demonstrated type-I band alignment with narrow conduction-band offset (CBO) and valence-band offset (VBO) of 0.35 and 0.45 eV, respectively, at the polycrystalline β-Ga 2 O 3 /In 2 O 3 interface, elucidating the potential of the above heterostructure for reducing the barrier height and enhancing carrier transport in visible-transparent oxide platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Band offsets have been reported for most relevant oxides on Ga 2 O 3 in search of candidate gate dielectrics for ultra-wide bandgap electronics. [16][17][18][19][20][21][22][23][24][25][26] In addition, common semiconductor heterojunctions have been reported as well, including Si, SiC, GaN, AlN, and IZGO. [27][28][29][30][31][32] Measuring band offsets for the InN/β-Ga 2 O 3 heterojunction is thus complementary to the reported results for the other III-Nitride materials AlN and GaN.…”
mentioning
confidence: 99%